Ultrasonographic study of the thumb pulleys and their entheses: correlations with anatomy and histology - Ingrid Moller; Maria Antonietta D’Agostino; Joan Blasi; Chiara Rizzo; Luis Coronel; David A. Bong; Maribel Miguel-Pérez; Juan Angel Patiño Galindo (RMD Open)
Objectives The entheseal nature of digital annular pulleys insertion was recently described, with high resolution ultrasound (US) reliably identifying these submillimetre structures with impressive accuracy. Since the thumb was not examined, the aim of the present study was to characterise the thumb annular pulley system, including entheses, from an anatomical, histological and ultrasonographic perspective.Methods US assessment and gross anatomical dissection were performed on cadaveric thumbs to investigate the thickness and structural features of the four thumb pulleys, including the identification of their entheses. US and anatomical measurements were correlated. Entheses identified by US were verified by histology. All thumb pulleys in healthy controls (HC) were detected and thickness was measured by US. A reliability exercise on US identification and anatomical study of thumb pulleys was carried out.Results 20 cadaveric thumbs and 40 thumbs from HC were examined. A total of 240 thumb pulleys (80 cadaveric, 160 HC) were analysed. The cadaveric study demonstrated good correlation between anatomical and US measurement of thumb pulleys thickness (r=0.8). Histology confirmed the entheseal nature of thumb pulleys insertions, with both fibrous and fibrocartilaginous features. 267/480 (55.6%) entheses were detected by US. A1 pulley entheses were always visualised while oblique pulley and A2 pulley entheses were seldom identified. The intrarater and inter-rater reliability showed good correlation among participants.Conclusions US is an effective and reliable tool to detect and study thumb pulleys, even though the identification of their entheses may be challenging and require advanced US skills.